Radiation therapy after radical surgery in prostate cancer - Paz-Manrique, R (2023)
Radiation therapy plays a key role in the treatment of prostate cancer on its own. For higher risk diseases, the risk of recurrence following single modality therapy increases and a combination of treatment modalities may be necessary to achieve optimal results. We review clinical outcomes of adjuvant and salvage radiotherapy following radical prostatectomy, including disease-free survival, cancer-specific survival and overall survival. We also discuss when best to intervene with post-prostatectomy radiotherapy.